Interaction between Nitrogen and Phosphate Stress Responses in Sinorhizobium meliloti - Hagberg, Kelly L.; Yurgel, Svetlana N.; Mulder, Monika; Kahn, Michael L. (Frontiers in Microbiology, 2016)
Bacteria have developed various stress response pathways to improve their assimilation and allocation of limited nutrients, such as nitrogen and phosphate. While both the Nitrogen Stress Response (NSR) and Phosphate Stress Response (PSR) have been studied individually, there are few experiments reported that characterize effects of multiple stresses on one or more pathways in Sinorhizobium meliloti, a facultatively symbiotic, nitrogen-fixing bacteria. The PII proteins, GlnB and GlnK, regulate the NSR activity, but analysis of global transcription changes in a PII deficient mutant suggest that the S. meliloti PII proteins may also regulate the PSR. PII double deletion mutants grow very slowly and pseudoreversion of the slow growth phenotype is common. To understand this phenomenon better, transposon mutants were isolated that had a faster growing phenotype. One mutation was in phoB, the response regulator for a two component regulatory system that is important in the PSR. phoB::Tn5 mutants had different phenotypes in the wild type compared to a PII deficient background. This led to the hypothesis that phosphate stress affects the NSR and conversely, that nitrogen stress affects the PSR. Our results show that phosphate availability affects glutamine synthetase activity and expression, which are often used as indicators of NSR activity, but that nitrogen availability did not affect alkaline phosphatase activity and expression, which are indicators of PSR activity. We conclude that the NSR is co-regulated by nitrogen and phosphate, whereas the PSR does not appear to be co-regulated by nitrogen in addition to its known phosphate regulation.